IMPACT STUDY OF THE BAN ON BAUXITE ORE EXPORT POLICY ON THE ECONOMY AND WELFARE OF THE COMMUNITY IN WEST KALIMANTAN - Gagas, Giorgia
Bauxite, as a non-renewable resource, requires optimal management to ensure its sustainable use. To develop domestic processing facilities and increase added value to bauxite, the government will implement a ban on bauxite ore exports starting from June 10, 2023. However, the unpreparedness of processing infrastructure to accommodate the entire bauxite production has raised concerns about the potential decline in bauxite production and its impact on local communities, such as those in West Kalimantan. West Kalimantan is the province with the largest bauxite reserves in Indonesia, and bauxite mining has played a crucial role in the economy of West Kalimantan in recent years. Therefore, this research aims to assess the benefits and drawbaks resulting from the bauxite export ban policy for local communities in West Kalimantan In this research, several scenarios will be compared, namely the export scenario under the existing bauxite processing plant conditions (Scenario 1), the implementation of an export ban policy with existing processing plant conditions (Scenario 2), the imposition of a bauxite export ban followed by an increase in bauxite processing plant capacity (Scenario 3), and the application of export relaxation until the completion of the bauxite processing plant construction (Scenario 4). To conduct the analysis, we utilized the 2016 West Kalimantan Input-Output Table, updated by distinguishing the bauxite mining sector from the mining and quarrying sector. Additionally, an econometric model was employed to model the social impacts measured by the Human Development Index (HDI). Based on the test results, it was found that the most significant economic and social impacts occurred under Scenario 4. During the forecast period from 2023 to 2027, the output impact amounted to 113.631 trillion Rupiah, encompassing a value-added impact of 78.876 trillion Rupiah and an indirect tax revenue impact of 781 billion Rupiah. Furthermore, Scenario 4 also resulted in employment absorption of 980,494 individuals. Based on the econometric model, Scenario 4 in 2027 had an HDI value of 71.83.